The Possibility to Use Modified Flight Ash as a Neutralizer in the Acid Soils Reclamation Processes = Możliwość zastosowania pyłu lotnego jako neutralizatora w procesach rekultywacji gleb kwaśnych - Ćwiąkała, Michał; Greinert, Andrzej; Kostecki, Jakub; Rafalski, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Using the alkaline fly ash after combustion of lignite as the acid soils neutralizer is a technique known for decades. Due to many disadvantages of the direct fly ash application it is sought to modify this material prior to its use. The process of fly ash modification in the magnetic activator involved breaking up fly ash to small grain sizes in order to obtain a material with a very large specific surface and modified properties.
Keywords: fly ash; magnetic activator; reclamation; soil neutralization; pył lotny; aktywator magnetyczny; rekultywacja; neutralizacja gleb